Macrofinancial Linkages of the Strategic Asset Allocation of Commodity-Based Sovereign Wealth Funds - Brown, Aaron Howard Clifford; Papaioannou, Michael; Petrova, Iva. (Washington, D.C. : International Monetary Fund, 2010)
This paper analyses the links between the investment strategies of a commodity-based SWF and the macroeconomic framework of the owner country. We examine some basic macrofinancial linkages of an SWF's strategic asset allocation (SAA) strategies with regard to the government budget, monetary policy, and exchange rate movements. Based on a simple Markowitz-model framework, which integrates the specific objectives and constraints facing an SWF and the country's specific characteristics and macroeconomic vulnerabilities (especially in relation to commodity prices and prospective defined liabilities), we derive an SAA. The asset-liability methodology that is applied in the selection of an SWF SAA also allows assessing whether (i) the SAA adequately takes into account the country-specific risks and vulnerabilities, and (ii) its objectives and macrofinancial constraints are consistent. Some analytical and practical issues in determining an SAA model are also discussed, along with key effects of a financial crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet